A Clinical Trial to Evaluate the Combined Effect of Ekavimshatika Guggulu and Bala Taila Matra Vasti in Sciatica (International Journal of Ayurveda and Pharma Research, 2025)
Ekavimshatika Guggulu is mentioned in Bhavaprakasha Madhyamakhanda Kushta Adhyaya and Bala Taila mentioned in Bhela Samhita Vata Vyadhi Adhyaya. Most of the drugs in Ekavimshatika Guggulu are of Vata-kapha Shamana and also mitigate Gridhrasi as per the Phalasruthy. Bala Taila is having Vatahara property and is Balya in nature. Matra Vasti possess the qualities of Vata Anulomana and Snehana properties. The study was an interventional study with pre and post-test, without control group. Subjects of either gender with age group 20-60 years registered in Pankajakasthuri Ayurveda Medical College & Post Graduate Centre, satisfying the inclusion and exclusion criteria were subjected to positive sampling and total of 27 subjects were selected and 27 subjects completed the clinical trial. The selected subjects were administered Ekavimshatika Guggulu in a dosage of 2 tablets orally thrice daily before food along with 75ml Bala Taila as Matra Vasti for 14 days. Assessment of the subjects was done on 0th day, 15th day and follow up done on 30th day with subjective and objective parameters. RESULTS: On analysing the results, it has been found that subjective parameters like tenderness, radiating pain, ODI scale, Sciatica Bothersomeness Index Scale, Sciatica Frequency Index Scale and objective parameters like SLR, Lessigues sign, also other parameters like Gridhrasi lakshanas got statistically significant improvement. Friedman test was used to assess the overall significance between three points. P-value